Between Physics and Metaphysics: Structure as a Boundary Concept - Tau, Ramiro (2015)
The notion of structure is found to be used in a great number of theories, scientific research programs and world views. However, its uses and definitions are as diverse as the objects of the scientific disciplines where it can be found. Without trying to recreate the structuralist aspiration from the mid XX century, which believed to have found in this notion a common transdisciplinary language, I discuss a specific aspect of this concept that could be considered a constant in different perspectives. This aspect refers to the location of the notions of structure as boundaries in the different scientific theories. With this, I try to argue that the definition or presentation of a structure configures in itself the frontier for scientific knowledge, defining at the same time implied ontological assumptions. In order to discuss this hypothesis, and taking into consideration the double origin of contemporary notions of structure –the mathematical and linguistic line–, I revise several theoretical perspectives which made explicit the relation between structures and knowledge, and their relation with the real: the arguments on physical knowledge by Eddington, structural anthropology, structural linguistics, Lacanian psychoanalysis and Piaget’s genetic psychology.